Transversality of the Gender Perspective: A Critical Look at the Study Programs of the Faculty of Social Sciences. How Far Have We Come? - Arias-Cascante, Nalda (2016)
This work corresponds to the project: “Analysis of Gender Mainstreaming in the Faculty of Social Sciences”. Our goal focuses on investigating how has implemented the gender perspective in the careers of the Faculty of Social Sciences? This proposal as the foundation welcomes political-institutional regulations of the National University, that bet by the inclusion of gender and equity as transverse axis to be assumed in the areas of academic. As a theoretical basis-methodological presents a research from some glances of academic women in the academy, based on the analysis of two dimensions: (1) gender as a transverse axis and (2) such as visibility of women in the academy. Evidence elucidates limitations with regard to mainstreaming in effective terms. Is still projecting stereotyped roles in teaching, and professionalization segregated by sex. This is a challenge that must be addressed the academy to respond to the dynamics of inequality that still by the transit of university women.